Sosialisasi Penanganan dan Pencegahan Stunting di Desa Cikaso Kecamatan Banjaranyar Kabupaten Ciamis - Fachmi Syam Arifin; Dedi Hermawan; Muhammad Rizqi Maulana; Dilla Triwulananzani; Futry Wella Fadillah (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Stunting is a serious health problem that affects the growth and development of children, especially in Cikaso Village, Banjaranyar District, Ciamis Regency. This article discusses the socialization of handling and prevention of stunting carried out in the village. Through a series of socialization activities to the community by providing an understanding of the importance of balanced nutrition and a healthy lifestyle to prevent stunting. The results of the socialization showed an increase in public awareness of the impact of stunting and active participation in nutrition programs. In addition, the nutritional assistance program and nutritious cooking training also succeeded in increasing family nutritional intake. This discussion emphasizes the importance of the involvement of all parties in efforts to prevent stunting to create a healthy and productive generation in the future. Thus, effective socialization can contribute significantly to reducing the prevalence of stunting in Cikaso Village.